2020
DOI: 10.1080/15548627.2020.1725405
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy is repressed during mitosis – seeing is believing

Abstract: For the last two decades there has been wide ranging debate about the status of macroautophagy during mitosis. Because metazoan cells undergo an "open" mitosis in which the nuclear envelope breaks down, it has been proposed that macroautophagy must be inhibited to maintain genome integrity. While many studies have agreed that the number of autophagosomes is greatly reduced in cells undergoing mitosis, there has been no consensus on whether this reflects decreased autophagosome synthesis or increased autophagos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Thus, they concluded that autophagy was not repressed, and some argued that the reduction in autophagosome number early in mitosis was a result of rapid clearance [14]. However, there are concerns with such strategies [18]. Briefly, LC3 is not sufficiently dynamic to accurately assess whether autophagosomes have originated in mitosis (which lasts 60-90 minutes) or the preceding interphase.…”
Section: Autophagy Initiation Is Repressed During Mitosismentioning
confidence: 99%
“…Thus, they concluded that autophagy was not repressed, and some argued that the reduction in autophagosome number early in mitosis was a result of rapid clearance [14]. However, there are concerns with such strategies [18]. Briefly, LC3 is not sufficiently dynamic to accurately assess whether autophagosomes have originated in mitosis (which lasts 60-90 minutes) or the preceding interphase.…”
Section: Autophagy Initiation Is Repressed During Mitosismentioning
confidence: 99%
“…PTAFR is found to be an antipsychotic target receptor potentially associated with pneumonia [ 35 ]. RPTOR plays an important role during mitosis [ 36 ]. The mutations in KCNJ2 cause genetic sudden cardiac death syndromes [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic inflammation is the most common factor leading to bone destruction in periodontitis. [ 38,39 ] Autophagy is basically a cellular recycling pathway that serves as a defense against various abnormal stimulations. [ 40 ] The development of periodontitis takes years, and autophagy is a dynamic process.…”
Section: Discussionmentioning
confidence: 99%